PROGRAM KREATIF BERBASIS PROJECT BERUPA MEDIA KALAM DALAM MENINGKATKAN KREATIVITAS SANTRI DI TPQ DESA SUKARAGAM - Fitria, Mawaddatul; Rizki Gunawan, Akmal; Marginingsih, Ria (Universitas Islam 45 Bekasi, 2024)
The project-based creative programme is an activity to increase the creativity of TPQ students in Sukaragam Village and give them the freedom to carry out these activities collaboratively and ultimately produce a product. The purpose of this programme is to stimulate the development of ideas, innovation and creativity in students and especially in teachers at TPQ. The lack of enthusiasm and learning spirit of TPQ students in Sukaragam Village is due to the teacher's lack of interest in learning, so the interest in reciting the Koran is very small. In addition, there is a lack of parental contribution in teaching their children to recite the Koran, thus creating children's unfamiliarity in involving themselves in recitation activities. The implementation method used is the training method which consists of three stages, namely the preparation stage, the implementation stage, and the evaluation stage. Thus, students have the potential to identify problems, formulate solutions collaboratively with teachers and children, and involve them actively in each stage of the process. This community service activity has a positive impact on teachers and students at TPQ Nurul Huda itself, namely being able to add skills and insights regarding creativity in learning. Then, it can tell the teachers at the TPQ that this creation can increase the interest and creativity of students, especially in the learning process.